Molecular epidemiology of carbapenem-resistant hypervirulent Klebsiella pneumoniae: risk factors and resistance mechanism of ceftazidime/avibactam in China - Wang, Na; Deng, Lexiu; Li, Huiying; Jia, Na; Peng, Xiaocui; Chang, Jianliang; Hao, Jiatong; Tang, Jianhua; Lei, Chunmei; Wang, Bu; Liu, Jianhua; Zhang, Wei (Frontiers in Cellular and Infection Microbiology, 2025)
BackgroundCarbapenem-resistant hypervirulent Klebsiella pneumoniae (CR-hvKP) represents a critical public health threat in China, characterized by the convergence of multidrug resistance and hypervirulence. The emergence of ceftazidime/avibactam (CZA) resistance further complicates clinical management. This study aimed to elucidate the molecular epidemiology, risk factors, and resistance mechanisms of CZA resistance in CR-hvKP across China, providing evidence for targeted interventions.MethodsA single-center molecular epidemiological analysis was conducted on 81 Carbapenem-resistant Klebsiella pneumoniae (CRKP) clinical isolates collected. All isolates underwent whole-genome sequencing for MultiLocus Sequence Typing, capsule typing, and identification of resistance genes (blaKPC-2 and blaNDM-1) and virulence factors (iucA, iroB, rmpA, rmpA2, and peg-344). CZA resistance mechanisms were investigated through broth microdilution minimum inhibitory concentration (MIC) testing and bioinformatics analysis. Galleria mellonella infection models were employed to assess virulence potential. Risk factors were analyzed using multivariate regression of clinical variables. Phylogenetic reconstruction employed single-nucleotide polymorphism-based analysis.ResultsST11 accounted for 96.15% (50/52) of CR-hvKP isolates, with K64 being the predominant capsule type (92.31%, 48/52). Additionally, 98.77% (80/81) of CRKP carried ≥1 virulence gene; 64.2% (52/81) of isolates with all five virulence genes exhibited lethality. Galleria mellonella revealed that the survival rate of CR-hvKP was lower than that of carbapenem-resistant non-hypervirulent Klebsiella pneumoniae (p<0.05). Antibiotic usage time (odds ratio [OR]=1.076, 95% confidence interval [CI]: 1.026–1.138), carbapenem antibiotic (OR = 0.117, 95% CI: 0.02266–0.4602), and malignant tumors (OR = 65.1, 95% CI: 7.078–1798) predicted CR-hvKP infection. Transferable blaKPC-2 on IncFII/IncR plasmids conferred CZA resistance (MIC>128 mg/L) without compromising carbapenem resistance, facilitated by a unique genetic context (TnpR_Tn3-ISKpn27-blaKPC-2-ISKpn6).ConclusionChina faces a rapid dissemination of ST11 CR-hvKP clones carrying diversified CZA resistance mechanisms. The convergence of hypervirulence and resistance in ST11 lineages—accelerated by invasive procedures and international transmission—demands enhanced genomic surveillance. CZA resistance arises through multiple pathways, necessitating combination therapies and stewardship programs limiting prolonged CZA use. Our findings underscore an urgent need for rapid diagnostics targeting emergent resistance determinants and infection control measures to contain high-risk clones.